Examine the whole baby to explain C-reactive protein elevation and hypercalcaemia. (29th September 2015) - Purayil, T; Kumar, Y; Burren, C
Abstract : Baby RD was born at term, weighing 4.78 kg (98–99.6 th centile) by emergency caesarean section for fetal distress and thick meconium. She was born in poor condition (Apgar 5 and 7) and required ventilation breaths. She developed signs of meconium aspiration soon after birth and needed 48h continuous positive airway pressure support. She was discharged from NICU on day 5 to the ward to continue antibiotics. Her C-reactive protein (CRP) peaked at 49 on day 2 and remained between 12 and 17 during week 1. Although clinically well and with no other evidence of infection, her CRP started rising on day 10 (CRP 27) and peaked at day 25 (CRP 69). Her repeated infection screen including viral PCR was negative. Antibiotics and topical antifungal were continued for suspected infection. It was also noted she had a rising calcium from day 10 (corrected Ca 3.1 mmol/l), peaking at 4.42 mmol/l at day 22. On day 22 she was noted to have faint indurated purplish bruising to the back, buttock and thigh. Dermatology review supported a clinical diagnosis of subcutaneous fat necrosis (SFCN) of newborn. Baby RD had no phenotypic features of William syndrome. PTH (<1 pmol/L) was appropriately suppressed, with normal 25-OH-vitamin D. However, 1, 25 (OH)2 vitamin D was significantly raised at 179 pmol/l (48–110). As she was clinically well, hypercalcaemia was initially managed with intravenous hydration with little effect. She was then given a single dose of IV pamidronate 0.5 mg/kg, which achieved significant reduction in corrected calcium to 3.1 mmol/l in 72 h. SFCN is a rare disorder producing characteristic purple or bluish nodules over the trunk, buttocks, thigh, arms and cheeks following a complicated delivery. Diagnosed clinically, it usually resolves within 3–6 months without medical intervention. Cases have been reported with severe hypercalcaemia hypothesised to be due to increased macrophage production of 1, 25(OH)2 vitamin D. The persistently elevated CRP is expected to reflect the inflammatory component of SFCN. The authors wish to highlight that marked hypercalcaemia is a rare complication of SFCN, there is an effective response to pamidronate and to emphasise the associated elevated CRP which caused prolonged antibiotic treatment and hospital stay.